PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSA PEMBELIAN PADA USAHA KOPI BUBUK GUNPAS DI KECAMATAN PANTI KABUPATEN PASAMAN - Sabrina; Septia Susanti (Adisam Publisher, 2026)
The escalating rivalry within the regional ground coffee sector compels business operators to maintain a robust brand image and product quality proficient in driving consumers' purchasing decisions. Kopi Bubuk Gunpas represents a regional ground coffee business situated throughout Panti District, Pasaman Regency, which has functioned across an extended duration yet continues encountering transactional instability stemming from market competition and shifting client dynamics. This investigation seeks to assess the impact of brand image and product quality regarding purchasing decisions within Kopi Bubuk Gunpas. The inquiry methodology executed adopts a numerical procedure featuring an empirical exploration layout. The aggregate population of this investigation encompasses every buyer obtaining products from Kopi Bubuk Gunpas across Panti District, Pasaman Regency, with an exhaustive selection mechanism administered. The compiled statistics were processed via multi-variable linear estimation models, backed by individual parameter tests and collective variance evaluations. The outcomes demonstrate that brand image exerts a constructive and meaningful influence on purchasing decisions. Product quality similarly yields a constructive and meaningful consequence on purchasing decisions. Concurrently, brand image and product quality generate a meaningful impact regarding buyers' purchasing decisions within Kopi Bubuk Gunpas. These discoveries signal that favorable evaluations of brand image and product quality constitute vital catalysts toward maximizing buyers' purchasing decisions.